THE PHYSIO ANATOMICAL VIEW OF KLEDAKA KAPHA (AYUSHDHARA, 2017)
Dosha, Dathu and Mala form the elemental cause of human body. Our body fails to exist without these three chief constituents. The concept of Tridosha is unique contribution of Ayurveda. They are Vata, Pitta and Kapha. These constitute the anatomical and physiological aspect of human body in general. Kapha is the element which gives stability and endurance to the body. There are 5 types of Kapha according to the location and function. Kledaka is one among them. It is located in Amashaya where the major part of digestion occurs. It is anatomically the stomach. Its function is to moisten and disintegrate the ingested food particles. It also protects the stomach from self digestion. It supports other Kapha sthanas of the body. According to its location and function given in Ayurvedic classics, its role in digestion can be assessed. When we consider the functions; Kledaka Kapha can be correlated with the gastric mucus which is secreted by surface epithelial cells of gastric mucosal layer and cells of gastric glands. The functions of gastric mucus are to lubricate the food particle for the formation of chime and to protect the gastric wall.The paper is intended to explore the physio anatomical aspect of Kledaka Kapha and its action as gastric mucus and its importance in digestion and metabolism of food.